2019
DOI: 10.1055/s-0039-1690159
|View full text |Cite
|
Sign up to set email alerts
|

[3+2]-Cycloaddition of α-Diazocarbonyl Compounds with Arenediazonium Salts Catalyzed by Silver Nitrate Delivers 2,5-Disubstituted Tetrazoles

Abstract: [3+2]-Cycloaddition of arenediazonium salts with diazo compounds (earlier exemplified only for trimethylsilyldiazomethane and 2,2,2-trifluorodiazoethane) has been developed to include a wide range of readily available α-diazocarbonyl compounds. The resulting 2-aryl-5-acyl-2H-tetrazoles are of high value in medicinal chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…A silver‐catalyzed [3+2] cycloaddition of α ‐diazocarbonyl compounds with arenediazonium tosylates was also reported by Krasavin and co‐workers (Scheme 40). [52] The arenediazonium tosylates which were used directly as obtained in the crude form from the diazotization reaction, reacted with diazocarbonyl compounds using 10 mol% AgNO 3 as the catalyst to generate various 2‐aryl‐5‐acyl‐2 H ‐tetrazoles in moderate to good yields with a broad substrate scope.…”
Section: Synthesis Of Tetrazolesmentioning
confidence: 99%
“…A silver‐catalyzed [3+2] cycloaddition of α ‐diazocarbonyl compounds with arenediazonium tosylates was also reported by Krasavin and co‐workers (Scheme 40). [52] The arenediazonium tosylates which were used directly as obtained in the crude form from the diazotization reaction, reacted with diazocarbonyl compounds using 10 mol% AgNO 3 as the catalyst to generate various 2‐aryl‐5‐acyl‐2 H ‐tetrazoles in moderate to good yields with a broad substrate scope.…”
Section: Synthesis Of Tetrazolesmentioning
confidence: 99%
“…Both 2 and 3 appeared suitable partners for a [3+2] cycloaddition reaction with arenediazonium salts. As reported recently by us and others such a reaction, catalyzed by silver(I) salts, provides a facile and regiospecific entry into medicinally important 2,5‐disubstituted tetrazoles. We reasoned that this cycloaddition, if successfully applied towards 2 and 3 , would deliver 2‐aryl tetrazol‐5‐yl sulfones 4 and sulfonamides 5 (Figureà).…”
Section: Introductionmentioning
confidence: 68%
“…Sulfonyl diazomethanes 2a – h , along with three sulfamoyl diazomethanes 3a – c prepared as described recently, were employed in the cycloaddition reactions with a series of arenediazonium tosylates 6a – k (Figureà) which had earlier been found to be stable and easy to handle non‐hygroscopic solid reagents and, importantly, proven efficient partners in similar cycloaddition reactions with acyl diazomethanes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…also reported the synthesis of 2‐aryl‐2 H ‐tetrazoles 159 via the [3 + 2] cycloaddition reaction of aryl diazonium salts with trimethylsilyldiazomethane (TMSCHN 2 ) by using excess silver salt and caesium fluoride (Scheme 40e). [ 191 ] Given the broad applicability and practicality of this tactic, there is no doubt that these reactions will find wide implications in tetrazole chemistry, meanwhile in‐depth mechanistic study and divergent regio‐control are also suggested to be put on the agenda. [ 192,193 ]…”
Section: Cyclization and Cycloaddition Reactions For The Constructionmentioning
confidence: 99%